Pengenalan Interaksi Alat Transportasi Umum Dengan Tempat Pemberhentian Pada Anak Usia Dini 4-6 Tahun Menggunakan Augmented Reality - Eka Yunita Anjayani; Emmy Wahyuningtyas; Beny Y.V Nasution (Melek IT : Information Technology Journal, 2016)
Introducing something at an early age children 4-6 years is certainly not easy. Likewise in kindergarten Wildani 2 Surabaya to introduce public transportation stops such as aircraft, ships, trains, buses and public transportation that are still using the two-dimensional image. To facilitate them in identifying and considering public transportation stop's using three-dimensional view and the animation is certainly more interesting for children to learn and easier to understand or know the form of public transportation with dismissal. This prompted the authors to try to show the model of public transportation with stops all forms of drawing a 3D augmented reality on smartphones that can help children to learn the public transportation. The app has a success rate of 68%, the introduction of learning media interaction of transport with stops for young children 4-6 years using Augmented Reality can be used as a new learning media, students are more interested to learn about the interaction of transportation stop's.